Risk factors for rifampicin-susceptible and isoniazid-resistant tuberculosis in adult patients with type 2 diabetes mellitus in Nanjing - Jing Guo; Xuebing Feng; Jialei Pang; Wenchao Li; Min Cai; Zhiyun Cao; Feishen Lin; Xia Zhang (BMC Infectious Diseases)
Abstract Objective Globally, Tuberculosis(TB) with type 2 diabetes mellitus (T2DM) is becoming increasingly serious, especially the emergence of rifampicin-susceptible and isoniazid-resistant tuberculosis (Hr-TB), which increases the difficulty of treatment and the burden of disease. Therefore, this single-center retrospective cohort study analyzed risk factors of Hr-TB in adult patients with T2DM and pulmonary tuberculosis (PTB) in Nanjing to guide clinical practice and improve the long-term prognosis of patients. Methods The clinical data of 279 adult inpatients diagnosed with culture-positive PTB and T2DM in the Second Hospital of Nanjing from January 2019 and December 2021 were collected. According to the drug susceptibility testing (DST) results, 44 patients with Hr-TB were categorized as the Hr-TB group, while the remaining 235 patients with drug-susceptible tuberculosis (DS-TB) were classified as DS-TB group. Hierarchical logistic regression was employed for multivariate analysis to identify variables associated with Hr-TB in patients with T2DM. Results There were no significant differences in age, sex, body mass index (BMI), smoking, drinking, ethnicity, education level, or comorbidities between the DS-TB and Hr-TB groups. Multivariate logistic regression analysis revealed that, history of previous tuberculosis treatment (OR = 2.348, 95%CI: 1.025 ~ 5.379, P = 0.044), poor FPG control (OR = 2.402, 95%CI: 1.208 ~ 4.776, P = 0.012), and serum iron levels ≥ 14.3µmol/l (OR = 2.808, 95%CI: 1.334 ~ 5.910, P = 0.007) are independent risk factors for Hr-TB in adult patients with T2DM in Nanjing. Within the cohort, 241 patients were Newly treatment tuberculosis patients, and among them, poor FPG control (OR = 2.296, 95%CI: 1.073 ~ 4.915, P = 0.032), and serum iron levels ≥ 14.3µmol/l (OR = 2.418, 95%CI: 1.048 ~ 5.577, P = 0.038) were identified as risk factors for Hr-TB. Conclusion Poor fasting glycemic control and serum iron levels ≥ 14.3µmol/L are independent risk factors for the development of Hr-TB in adults with T2DM and PTB, moreover, the contribution of these as risk factors were more pronounced in the newly treatment tuberculosis patients subgroup than patients with a history of previous tuberculosis treatment. History of previous tuberculosis treatment was also found to be a risk factor for Hr-TB in adults with T2DM.